A three-dimensional multiphase composite material and its preparation method and application in electromagnetic wave absorption

By electrochemical treatment and nanostructure synthesis on carbon fibers, a three-dimensional multi-phase composite material was prepared, which solved the problem of poor CF impedance matching performance and significantly improved its electromagnetic wave absorption performance.

CN116904039BActive Publication Date: 2025-04-25SHANDONG ICD HIGH PERFORMANCE FIBRES CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310872963.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-04-25
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

When carbon fiber (CF) is an electromagnetic wave absorbing material, its high conductivity leads to poor impedance matching performance, which limits its application.

Method used

The carbon fibers were treated by electrochemical anodization, wrapped with magnetic Co3O4 and partially reduced to Co nanoparticles, combined with catalytic growth of carbon nanofibers and carbon nanotubes, and finally mixed with paraffin to prepare a three-dimensional multiphase composite material Co3O4/Co@CNFs/CNTs/CF/paraffin.

Benefits of technology

It significantly improves the electromagnetic wave absorption capacity of CF, optimizes the impedance matching performance, achieves higher absorption strength and wider effective absorption bandwidth, and is suitable for the electromagnetic wave absorption field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116904039B_ABST
    Figure CN116904039B_ABST
Patent Text Reader

Abstract

The present invention discloses a three-dimensional multiphase composite material and its preparation method and application in electromagnetic wave absorption, belonging to electromagnetic wave absorbing materials. The present invention wraps magnetic Co3O4 on the surface of resistive absorbing material CF by low-temperature pyrolysis of ZIF‑67, and partially reduces Co3O4 to Co, catalyzes the growth of CNFs and CNTs during the CVD process, and finally mixes with paraffin to obtain a multi-composite material Co3O4 / Co@CNFs / CNTs / CF / paraffin, so that the wave absorption performance of the CF material is significantly improved. The present invention can significantly optimize the impedance matching coefficient of CF by regulating the morphology and structure of Co3O4 / Co@CNFs / CNTs / CF, and obtain both dielectric and magnetic losses at the same time, providing a simple and mass production strategy for the development of light-weight, thin-thickness CF-based strong electromagnetic absorbing materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electromagnetic wave absorbing materials, and specifically relates to a three-dimensional multiphase composite material and a preparation method thereof and application in electromagnetic wave absorption. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Since the existence of electromagnetic waves was confirmed in the 19th century, they have been widely known and used, ushering in a new era of radio electronic technology. Electromagnetic interference and radiation have therefore become ubiquitous, causing a series of adverse effects on human health, the natural environment, information storage, equipment performance, military stealth, etc. The World Health Organization has officially identified electromagnetic radiation pollution as the fourth largest source of pollution after water pollution, air pollution, and noise pollution. This has prompted researchers to develop electromagnetic wave absorbing materials with high-efficiency absorption performance, wide effective bandwidth absorption, light weight, thin thickness, easy to manufacture, and multifunctional. The improvement of the wave absorbing industry is also imminent.

[0004] Electromagnetic wave absorbing materials can capture electromagnetic waves into the interior of the material, and effectively convert electromagnetic waves into heat or magnetic energy through dielectric loss or magnetic loss, thereby reducing the reflection and transmission of electromagnetic waves. At present, according to the loss mechanism of the material, electromagnetic wave absorbers can be divided into three types: resistive type, dielectric type and magnetic dielectric type. Resistive absorbers mainly include carbon black, graphite, CNTs, CF, etc., which mainly absorb electromagnetic waves through interaction with the electric field. The absorption efficiency depends on the conductivity and dielectric constant of the material. They show obvious advantages in low density and high stability, but impedance mismatch often limits their application. Dielectric absorbers such as inorganic ceramics and semiconductors mainly absorb electromagnetic waves through dielectric polarization loss. This type of material has excellent thermal stability, but the lower attenuation capacity limits the improvement of absorption intensity. The attenuation of electromagnetic waves by magnetic dielectric absorbers mainly comes from eddy current loss, natural resonance and exchange resonance. For example, magnetic metals, magnetic oxides, magnetic sulfides, etc. can be used to reduce matching thickness, but are often limited by deficiencies such as high density and inherent impedance mismatch. In order to overcome the shortcomings of the above-mentioned single-component absorbing materials, the design and preparation of multi-component absorbing materials has become an inevitable choice. At the same time, it is also necessary to further explore a new generation of high-efficiency electromagnetic wave absorbing materials.

[0005] CF, one of the carbon-based materials, has the advantages of high strength, high modulus, excellent mechanical properties, and is often used as a reinforcement for composite materials. At present, most of the research on CF at home and abroad focuses on its mechanical properties, while ignoring its potential application value in the field of electromagnetic wave absorption. CF is a resistive absorbing material with a large aspect ratio, significant shape anisotropy, and strong conductivity loss. However, the excessively high conductivity and high complex dielectric constant of CF cause more electromagnetic waves to be reflected rather than propagated into the absorbing material, resulting in poor impedance matching, which to a certain extent limits its application as an electromagnetic wave absorber. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide a method that can simply and effectively improve the problem of poor impedance matching performance caused by high conductivity when CF is used as an absorbing material, and to improve the electromagnetic wave dissipation capacity of CF. To this end, the present invention provides a three-dimensional multiphase composite material, a preparation method thereof, and an application in electromagnetic wave absorption.

[0007] In order to achieve the above object, the technical solution of the present invention is:

[0008] The first aspect of the present invention provides a method for preparing a three-dimensional multiphase composite material, comprising the following steps:

[0009] Step 1: Place the unsized carbon fiber CF in an aqueous solution of ammonium dihydrogen phosphate for electrochemical anodization, and then wash and dry;

[0010] Step 2: synthesizing ZIF-67 with cobalt salt and 2-methylimidazole to obtain a ZIF-67 suspension;

[0011] Step 3: Place the CF dried in step 1 into the ZIF-67 suspension and let stand for 1 to 2 hours, take it out and dry it to obtain ZIF-67@CF;

[0012] Step 4: placing the ZIF-67@CF into a tubular chemical vapor deposition furnace, heating to 300-400° C. in an air atmosphere, keeping the temperature for 0.5-2 h, and cooling to room temperature to obtain Co3O4@CF;

[0013] Step 5: Place the Co3O4@CF in a tubular chemical vapor deposition furnace with a temperature raised to 400-500°C, and under the protection of N2, introduce 0.1-0.3L / min H2 to reduce part of the Co3O4 to Co nanoparticles for 10-30min to obtain Co3O4 / Co@CF; then continue to heat to 600-700°C, and catalytically grow carbon nanofibers CNFs and carbon nanotubes CNTs in an atmosphere of 0.05-0.15L / min H2 and 0.1-0.15L / mi C2H2 to obtain a three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material.

[0014] The present invention uses a simple low-temperature pyrolysis method of ZIF-67 to wrap magnetic Co3O4 on the surface of the resistive absorbing material CF, and partially reduces Co3O4 to Co, catalyzes the growth of CNFs and CNTs during the CVD process, and finally mixes with paraffin to obtain a multi-composite material Co3O4 / Co@CNFs / CNTs / CF / paraffin, thereby significantly improving the absorbing performance of the CF material.

[0015] In some embodiments of the present invention, in step 1, the concentration of the aqueous solution of ammonium dihydrogen phosphate is 5 wt.%.

[0016] In some embodiments of the present invention, in step 1, the electrochemical anodizing treatment comprises the following steps: CF is continuously passed through an electrolytic cell, graphite is used as a cathode to undergo a reduction reaction, and CF is used as an anode to be oxidized to generate a rough and chemically active surface.

[0017] The current and oxidation time can be adjusted. The current is 0.1-0.3A, and the oxidation time is 2-6min. Preferably, electrochemical anodization is performed for 4min at a current of 0.2A. When the current and oxidation time are adjusted, the charge amount participating in the electrode reaction is ensured to be the same.

[0018] In some embodiments of the present invention, the synthesis of ZIF-67 from cobalt salt and 2-methylimidazole comprises the following steps:

[0019] The cobalt salt and 2-methylimidazole were dissolved in a solvent respectively and dispersed evenly by ultrasound. Then, the cobalt salt solution was quickly poured into the 2-methylimidazole solution and stirred continuously at room temperature to synthesize ZIF-67.

[0020] Preferably, the cobalt salt is cobalt nitrate hexahydrate, and the molar ratio of the cobalt salt to 2-methylimidazole is 1:8 to 1:4; more preferably 1:8.

[0021] Preferably, the ultrasonic time is 0.5 to 2 h, more preferably 0.5 h.

[0022] Preferably, the solvent is methanol or deionized water, more preferably deionized water.

[0023] Preferably, the stirring time is 10 to 30 min, more preferably 10 min.

[0024] In some embodiments of the present invention, in step 3, the air-drying is performed at room temperature for 24 to 48 hours.

[0025] In some embodiments of the present invention, in step 4, the temperature is heated to 300-400° C. at a heating rate of 2-5° C. / min in an air atmosphere, preferably 5° C. / min, and the heating temperature is preferably 350° C. Meanwhile, the holding time is preferably 0.5 h.

[0026] In some embodiments of the present invention, in step 5, under the protection of N2, 0.1 L / min of H2 is introduced to reduce part of Co3O4 to Co nanoparticles, and the reduction time is 10 min.

[0027] In some embodiments of the present invention, in step 5, the temperature is continued to be raised to 650° C., and the catalytic growth of CNFs and CNTs is carried out for 30 minutes in an atmosphere of 0.05 L / min H2 and 0.1 L / mi C2H2.

[0028] In some embodiments of the present invention, the method for preparing the three-dimensional multiphase composite material also includes: grinding the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material into powder and mixing it with solid paraffin to obtain Co3O4 / Co@CNFs / CNTs / CF / paraffin material.

[0029] Among them, the mass proportion of Co3O4 / Co@CNFs / CNTs / CF in Co3O4 / Co@CNFs / CNTs / CF / paraffin material is 10-35wt.%.

[0030] The second aspect of the present invention provides a three-dimensional multiphase composite material, which is prepared according to the above-mentioned method for preparing the three-dimensional multiphase composite material.

[0031] Among them, Co3O4 and Co, as magnetic dielectric absorbers, can reduce the matching thickness of the absorber when compounded with CF, optimize its electromagnetic parameters so that the composite material can obtain better impedance matching characteristics. The growth of CNFs and CNTs can help build a rich three-dimensional network structure, provide sufficient electron transitions, migration paths, and multiple reflections and scattering polarizations. Paraffin is a typical wave-transmitting material, which is conducive to the entry of electromagnetic waves into the material.

[0032] The third aspect of the present invention provides application of the above three-dimensional multiphase composite material in the field of electromagnetic wave absorption.

[0033] The beneficial effects of the present invention are:

[0034] The present invention provides a method that is simple to operate, has high production efficiency, can effectively improve the poor impedance matching performance caused by high conductivity when CF is used as an absorbing material, and significantly improves the electromagnetic wave absorption capacity of CF. The method can significantly optimize the impedance matching coefficient of CF by regulating the morphology and structure of Co3O4 / Co@CNFs / CNTs / CF, and simultaneously obtain dielectric (multiple reflections and scattering, rich interfaces and conductive networks, and appropriate defects) and magnetic dual losses. It also solves the problem that the existing process operation is complicated and cannot meet the needs of industrial production, and provides a simple and mass production strategy for the development of light-weight, thin-thickness CF-based strong electromagnetic absorbing materials.

[0035] It has been tested that within the test range of 2-18 GHz, the three-dimensional multiphase composite material of the present invention achieves higher absorption intensity at a thinner thickness, and the effective absorption bandwidth can stably reach above 4 GHz. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0037] Figure 1 This is a scanning electron microscope image of the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material obtained in Example 1 of the present invention;

[0038] Figure 2 Scanning electron microscope image of the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material of Inventive Example 2. DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0040] Example 1

[0041] A method for preparing a three-dimensional multiphase composite material comprises the following steps:

[0042] Step 1: Place unsized carbon fiber (CF) into a 5 wt.% aqueous solution of ammonium dihydrogen phosphate, electrochemically anodize for 4 min at a current of 0.2 A, and then wash and dry.

[0043] Step 2: Dissolve 2.91 g of cobalt nitrate hexahydrate and 6.57 g of 2-methylimidazole in 200 mL of deionized water respectively and ultrasonicate for 0.5 h to make them evenly dispersed. Then, pour the cobalt nitrate aqueous solution into the 2-methylimidazole aqueous solution quickly and stir continuously at room temperature for 10 min to synthesize ZIF-67 and obtain a ZIF-67 suspension.

[0044] Step 3: Place the CF obtained in step 1 into the ZIF-67 suspension prepared in step 2 and let it stand for 1 hour. Take it out and dry it at room temperature for 24 hours to obtain ZIF-67@CF.

[0045] Step 4: Place the ZIF-67@CF obtained in step 3 into a tubular chemical vapor deposition (CVD) furnace, heat to 350°C at a heating rate of 5°C / min in an air atmosphere, keep warm for 2 hours, cool to room temperature, take out the sample, and obtain Co3O4@CF.

[0046] Step 5: The Co3O4@CF obtained in step 4 is placed in a tubular CVD furnace with a temperature raised to 450°C. Under the protection of N2, 0.1L / min of H2 is introduced to reduce part of the Co3O4 to Co nanoparticles for 10 minutes. The temperature is then continued to rise to 650°C, and carbon nanofibers (CNFs) and carbon nanotubes (CNTs) are catalytically grown in an atmosphere of 0.05L / min H2 and 0.1L / mi C2H2 for 30 minutes to obtain a three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material.

[0047] Step 6: Grind the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material obtained in step 5 into powder and mix it with solid paraffin to prepare a paraffin composite (Co3O4 / Co@CNFs / CNTs / CF / paraffin) for application in the field of electromagnetic wave absorption.

[0048] The product powder (25wt.%) was uniformly mixed with solid paraffin and pressed into a coaxial pattern with an outer diameter of 7.00mm, an inner diameter of 3.04mm and a thickness of 2.00mm. The wave absorption performance was tested with an Agilent TE5071C vector network analyzer at a test frequency of 2-18GHz. The minimum reflection loss of Co3O4 / Co@CNFs / CNTs / CF / paraffin was measured to be -60.85dB (1.22mm) and the effective absorption bandwidth was 4.24GHz (1.38mm) (the minimum reflection loss of untreated unsizing CF / paraffin was -26.59dB (1.75mm) and the effective absorption bandwidth was 4.24GHz (1.35mm)).

[0049] Figure 1This is a scanning electron microscope image of the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material obtained in Example 1 of the present invention.

[0050] Example 2

[0051] A method for preparing a three-dimensional multiphase composite material comprises the following steps:

[0052] Step 1: Place unsized carbon fiber (CF) into a 5 wt.% aqueous solution of ammonium dihydrogen phosphate, electrochemically anodize at a current of 0.2 A for 4 min, and then wash and dry.

[0053] Step 2: Dissolve 2.91 g of cobalt nitrate hexahydrate and 6.57 g of 2-methylimidazole in 200 mL of deionized water respectively and ultrasonicate for 0.5 h to make them evenly dispersed. Then, pour the cobalt nitrate aqueous solution into the 2-methylimidazole aqueous solution quickly and stir continuously at room temperature for 10 min to synthesize ZIF-67 and obtain a ZIF-67 suspension.

[0054] Step 3: Place the CF obtained in step 1 into the ZIF-67 suspension prepared in step 2 and let it stand for 1 hour. Take it out and dry it at room temperature for 24 hours to obtain ZIF-67@CF.

[0055] Step 4: Place the ZIF-67@CF obtained in step 3 into a tubular chemical vapor deposition (CVD) furnace, heat to 350°C at a heating rate of 5°C / min in an air atmosphere, keep warm for 2 hours, cool to room temperature, take out the sample, and obtain Co3O4@CF.

[0056] Step 5: The Co3O4@CF obtained in step 4 is placed in a tubular CVD furnace with a temperature raised to 450°C. Under the protection of N2, 0.1L / min of H2 is introduced to reduce part of the Co3O4 to Co nanoparticles for 10 minutes. The temperature is then raised to 700°C, and carbon nanofibers (CNFs) and carbon nanotubes (CNTs) are catalytically grown in an atmosphere of 0.05L / min H2 and 0.1L / mi C2H2 for 30 minutes to obtain a three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material.

[0057] Step 6: Grind the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material obtained in step 5 into powder and mix it with solid paraffin to prepare a paraffin composite (Co3O4 / Co@CNFs / CNTs / CF / paraffin) for application in the field of electromagnetic wave absorption.

[0058] The product powder (25wt.%) was uniformly mixed with solid paraffin and pressed into a coaxial sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm and a thickness of 2.00mm. The wave absorption performance was tested with an Agilent TE5071C vector network analyzer at a test frequency of 2-18GHz. The minimum reflection loss of Co3O4 / Co@CNFs / CNTs / CF / paraffin was measured to be -49.46dB (1.15mm) and the effective absorption bandwidth was 4.08GHz (1.28mm).

[0059] Figure 2 This is a scanning electron microscope image of the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material obtained in Example 2 of the present invention.

[0060] Table 1

[0061]

[0062]

[0063] Table 1 shows the X-ray diffraction pattern information of the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material obtained in Examples 1 and 2 of the present invention. As shown in Table 1, all samples have obvious characteristic diffraction peaks near 2θ=26° and 2θ=44°, corresponding to the (002) crystal plane of graphite C and the (400) crystal plane of Co3O4, respectively. The weaker diffraction peaks at 2θ=51° and 2θ=76° correspond to the (200) and (220) crystal planes of Co, respectively, verifying the presence of metallic Co. The X-ray diffraction results indirectly prove the successful synthesis of the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material.

[0064] Table 2

[0065]

[0066] Table 2 shows the magnetic properties test curve information of the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material obtained in Examples 1 and 2 of the present invention. Due to the residual magnetic metal Co and magnetic metal oxide Co3O4, the sample exhibits weak ferromagnetic activity under magnetic field excitation, and its hysteresis loop is type IV. As shown in Table 2, the saturation magnetization intensity M of Examples 1 and 2 is S are 4.70 and 3.03emu / g respectively, and the coercivity H C The M of Example 1 is 423.17 Oe and 170.68 Oe respectively. S The value is the highest, corresponding to the largest content of magnetic material, which is beneficial to improve the magnetic loss. In addition, the H CThe value is much larger than 10Oe of bulk Co, which will shift the natural resonance peak to GHz frequency and help to obtain satisfactory absorbing performance in the range of 2-18GHz.

[0067] Table 3

[0068]

[0069] Table 3 shows the electromagnetic wave absorption performance of untreated unsized CF (labeled as 0) and the three-dimensional multiphase composite materials of Examples 1 and 2, showing their minimum reflection loss (RL min ) and effective absorption bandwidth (EAB), and their corresponding frequency band (f) and thickness (t). As can be seen from Table 3, within the test range of 2-18 GHz, the embodiment achieves higher absorption intensity at a thinner thickness, and the effective absorption bandwidth can stably reach more than 4 GHz, verifying its potential application value. Overall, the wave absorption performance of Example 1 is better than that of Example 2. The excellent performance is derived from the formation of CNFs and CNTs with appropriate diameters, high degree of graphitization, appropriate defects, rich and uniform at an appropriate temperature of 650°C. The presence of Co3O4 and Co also optimizes impedance matching while increasing magnetic losses. The formation of a three-dimensional conductive network between the above materials and CF is also beneficial to improving the wave absorption performance of the material.

[0070] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a three-dimensional multiphase composite material, characterized in that: The following steps are involved: Step 1: Put the unsized carbon fiber CF into an aqueous solution of ammonium dihydrogen phosphate for electrochemical anodization, and then wash and dry; Step 2: synthesizing ZIF-67 with cobalt salt and 2-methylimidazole to obtain a ZIF-67 suspension; Step 3: Place the CF dried in step 1 into the ZIF-67 suspension and let stand for 1 to 2 hours, take it out and dry it to obtain ZIF-67@CF; Step 4: placing the ZIF-67@CF into a tubular chemical vapor deposition furnace, heating to 300-400° C. in an air atmosphere, keeping the temperature for 0.5-2 h, and cooling to room temperature to obtain Co3O4@CF; Step 5: Put the Co3O4@CF into a tubular chemical vapor deposition furnace with a temperature of 400-500°C, and under the protection of N2, introduce 0.1-0.3L / min H2 to reduce part of the Co3O4 to Co nanoparticles for 10-30min to obtain Co3O4 / Co@CF; then continue to heat to 600-700°C, and catalytically grow carbon nanofibers CNFs and carbon nanotubes CNTs in an atmosphere of 0.05-0.15L / min H2 and 0.1-0.15L / mi C2H2 to obtain a three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material; The synthesis of ZIF-67 from cobalt salt and 2-methylimidazole includes the following steps: The cobalt salt and 2-methylimidazole were dissolved in a solvent respectively and dispersed evenly by ultrasound, and then the cobalt salt solution was quickly poured into the 2-methylimidazole solution and stirred continuously at room temperature to synthesize ZIF-67; The cobalt salt is cobalt nitrate hexahydrate, and the molar ratio of the cobalt salt to 2-methylimidazole is 1:8 to 1:4; The ultrasonic time is 0.5 to 2 hours; the solvent is methanol or deionized water; and the stirring time is 10 to 30 minutes.

2. The method for preparing a three-dimensional multiphase composite material according to claim 1, characterized in that: In step 1, the concentration of the aqueous solution of ammonium dihydrogen phosphate is 5 wt.%.

3. The method for preparing a three-dimensional multiphase composite material according to claim 1, characterized in that: In step 1, the electrochemical anodizing treatment comprises the following steps: CF continuously passes through the electrolytic cell, graphite acts as the cathode to undergo reduction reaction, and CF acts as the anode to be oxidized to generate a rough and chemically active surface; Among them, the current is 0.1-0.3A, and the oxidation time is 2-6min.

4. The method for preparing a three-dimensional multiphase composite material according to claim 3, characterized in that: In step 1, electrochemical anodization is performed at a current of 0.2 A for 4 minutes. The current magnitude and oxidation time are adjusted to ensure that the amount of charge participating in the electrode reaction is the same.

5. The method for preparing a three-dimensional multiphase composite material according to claim 1, characterized in that: In step 3, the drying is performed at room temperature for 24 to 48 hours.

6. The method for preparing a three-dimensional multiphase composite material according to claim 1, characterized in that: In step 4, the temperature is heated to 300-400° C. at a heating rate of 2-5° C. / min in an air atmosphere.

7. The method for preparing a three-dimensional multiphase composite material according to claim 1, characterized in that: In step 5, under the protection of N2, 0.1 L / min of H2 was introduced to reduce part of Co3O4 to Co nanoparticles, and the reduction time was 10 min.

8. The method for preparing a three-dimensional multiphase composite material according to claim 1, characterized in that: In step 5, the temperature is continued to be raised to 650°C, and the catalytic growth of CNFs and CNTs is carried out in an atmosphere of 0.05 L / min H2 and 0.1 L / mi C2H2 for 30 min.

9. The method for preparing a three-dimensional multiphase composite material according to claim 1, characterized in that: The method further comprises grinding the three-dimensional Co3O4 / Co@CNFs / CNTs / CF composite material into powder and mixing the powder with solid paraffin to obtain a Co3O4 / Co@CNFs / CNTs / CF / paraffin material; Among them, the mass proportion of Co3O4 / Co@CNFs / CNTs / CF in Co3O4 / Co@CNFs / CNTs / CF / paraffin material is 10-35wt.%.

10. A three-dimensional multiphase composite material, characterized in that: The three-dimensional multiphase composite material is prepared according to the preparation method of any one of claims 1 to 9.

11. Use of the three-dimensional multiphase composite material according to claim 10 in the field of electromagnetic wave absorption.